Self-Compassion dan Psychological Well-Being pada Pasien Kanker - Sihombing, Ratna M.; Nuraini, Tuti; Afiyanti, Yati (Journal of Telenursing (JOTING), 2024)
This study aims to examine the relationship between self-compassion and the psychological well-being of cancer patients. The method used in this research is a systematic review, where we conducted journal searches in the ScienceDirect, PubMed, ProQuest, Springer, and EBSCOhost databases using the keywords' cancer patients', 'psychological well-being, 'and 'self-compassion. ' The research results show that self-compassion influences levels of depression, stress, anxiety, quality of life, body image disturbance, body shame, stigma, and other things that affect the psychology of cancer patients. In conclusion, there is a relationship between self-compassion and psychological well-being in cancer patients.This study aims to examine the relationship between self-compassion and the psychological well-being of cancer patients. The method used in this research is a systematic review, where we conducted journal searches in the ScienceDirect, PubMed, ProQuest, Springer, and EBSCOhost databases using the keywords' cancer patients', 'psychological well-being, 'and 'self-compassion. ' The research results show that self-compassion influences levels of depression, stress, anxiety, quality of life, body image disturbance, body shame, stigma, and other things that affect the psychology of cancer patients. In conclusion, there is a relationship between self-compassion and psychological well-being in cancer patients. Keywords: Cancer Patients, Psychological Well-Being, Self-Compassion